Study of lean system higher education institutions practices and lean system outcome - Tarar, Mariam Altaf (2023)
Lean system application is successfully recognised in manufacturing sector. However, its implementation in HEIs is at nascent stage. This research investigates Leans system particularly in HEIs context for imbibing quality excellence. The research aims to empirically investigate the Lean System Higher Education Institution (LSHEIs) practices and Lean System Outcome (LSO). For this purpose, the LSHEIs practices in teaching processes and LSO are identified. This research provides insights into the Lean system in the HEIs through qualitative method. On basis of literature review, the theory is developed for LSHEIs Practices and LSO. The qualitative study is conducted through semi-structured interviews to identify practices of LSHEIs and potential LSO. The LSHEIs practices categorised under four Lean Principle Levels i.e. Philosophy, Process, People and Partners and Continuous Improvement. Qualitative results identified 94 codes for LSHEIs practices and LSO. The result provides the evidence of the relationship of the LSHEIs practices and LSO, and supports the literature. The results helped to conceptualize study on the developing countries and filling gap of limited researches on Lean system in HEIs. It will help higher education institutions to improve and other researchers and practitioners to expand knowledge in this area.